Assessment of Selected Aspects of Safety Management In The Organization of Mass Events: A Case Study of a Football Club in Poland - Tomasz EWERTOWSKI; Nina KROLL; Jakub FENSTER (Communications of International Proceedings, 2024)
This article was motivated by the need to address the knowledge gap identified in the literature analysis. The purpose of this article is to present an assessment of the safety of spectators attending a football match held at the stadium of one of Poland’s sports clubs. The analysis focused on three selected aspects of safety management: security provided by information and security services, medical safety, and the safety of the venue and its infrastructure. Additionally, a fourth aspect—spectators' sense of safety—was included in the analysis. The study was preceded by a review of literature on the subject matter. The research tools used included a semi-structured interview, observation, an internal audit based on a prepared checklist, and a questionnaire survey. The combination of these research methods allowed for the use of triangulation to enhance the reliability of the study. Furthermore, a custom five-point rating scale was developed, which was used to assess both the overall level of safety at the mass event and management of its individual aspects. Based on the results, it was determined that the overall safety management level at the analyzed stadium ranged between 4 and 5, which corresponds to a range between acceptable and broadly acceptable risk. However, it is important to note the existence of a 'bottleneck' in this assessment, represented by the aspect of spectators' sense of safety, which received an average rating of 3.43, indicating tolerable risk. Several possible improvements have been proposed to enhance safety levels in this particular area.
Keywords: mass event; security; safety management; risk management